2007
DOI: 10.2307/25065859
|View full text |Cite
|
Sign up to set email alerts
|

Polyphyly of Polycarpon (Caryophyllaceae) inferred from DNA sequence data

Abstract: Guatteria (Annonaceae) is with ca. 265 species one of the largest genera of Neotropical trees together with Inga and Ocotea. Use of Guatteria in evolutionary studies has been hampered by taxonomic problems caused by lack of morphological variability in the genus. This study focuses on molecular phylogenetic relationships within Guatteria and its satellites Guatteriopsis, Guatteriella and Heteropetalum, and implications of these relationships for classification and character evolution. Results show that Guatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
(45 reference statements)
0
25
1
1
Order By: Relevance
“…and Heteropetalum Benth. The close affinity between these genera was established by many authors independently on morphological grounds (for details see Erkens et al 2007a, Erkens & Maas 2008 and via more formal (molecular or morphological) phylogenetic analyses (He et al 1999, Bygrave 2000. However, none of the latter studies had sufficient taxon sampling or enough data to adequately address the putative monophyly of these four genera.…”
Section: The Former Guatteria Groupmentioning
confidence: 99%
See 3 more Smart Citations
“…and Heteropetalum Benth. The close affinity between these genera was established by many authors independently on morphological grounds (for details see Erkens et al 2007a, Erkens & Maas 2008 and via more formal (molecular or morphological) phylogenetic analyses (He et al 1999, Bygrave 2000. However, none of the latter studies had sufficient taxon sampling or enough data to adequately address the putative monophyly of these four genera.…”
Section: The Former Guatteria Groupmentioning
confidence: 99%
“…However, none of the latter studies had sufficient taxon sampling or enough data to adequately address the putative monophyly of these four genera. This question was specifically addressed in a molecular phylogenetic study and it was shown that Guatteriopsis, Guatteriella and Heteropetalum were actually nested within Guatteria (Erkens et al 2007a). As a result the nested genera were transferred into Guatteria (Erkens & Maas 2008).…”
Section: The Former Guatteria Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…The first dataset is from a recent molecular phylogenetic study (Erkens et al 2007) of the large Neotropical tree genus Guatteria Ruiz & Pav. (Annonaceae; Magnoliales, 'magnoliids').…”
mentioning
confidence: 99%